Acute effects of plyometric warm-up with different box heights on sprint and agility performance in national-level field hockey athletes - Sener, T.; Sozbir, K.; Karli, U. (Isokinetics and Exercise Science, 2021)
BACKGROUND: Postactivation potentiation (PAP) is an acute and temporary enhancement of muscular performance resulting from previous muscular contraction. Extensive research exists examining the PAP effect after a heavy resistance exercise but there is limited research examining the PAP effect after a plyometric stimulus to the pre-competition practices (e.g., warm-up) of well-trained athletes. OBJECTIVE: The purpose of this study was to investigate the acute effects of plyometric warm-up with different box heights on sprint and agility performance in national-level field hockey athletes at recovery time of immediately, 5 minutes and 10 minutes. METHODS: In a randomized crossover design, ten male national-level field hockey athletes performed 30-m sprint (with 10-m split) and agility test at baseline, immediately (~ 15 sec), 5 minutes and 10 minutes after a high-intensity plyometric warm-up (HIPW), a low-intensity plyometric warm-up (LIPW) and a control trial (CT). RESULTS: Mean 10-m sprint times, 30-m sprint times and agility times were similar between trials at baseline (p > 0.05). Significant trial x time interactions (p < 0.05) were observed for 10-m sprint time, 30-m sprint time and agility time. 10-m sprint times were significantly decreased after HIPW at all time-points and LIPW at immediately time-point, relative to baseline (p < 0.05). HIPW 10-m sprint times were faster at all time-points and LIPW sprint time was faster at 10 minutes when compared with CT (p ? 0.05). Thirty-meter sprint times were significantly decreased after HIPW and LIPW at all time-points, relative to baseline (p < 0.05). HIPW 30-m sprint times at all time-points and LIPW at both the 5 and 10 minute time-points were faster than CT (p < 0.05). Agility times were significantly decreased after HIPW at all time-points and LIPW at both the immediately and 5 minutes time-points, relative to baseline (p < 0.05). HIPW and LIPW agility times were faster than CT, at all time-points (p < 0.05). CONCLUSIONS: Both HIPW and LIPW may be effective in enhancing the pre-training or pre-competition practices in off-season for national-level field hockey athletes. However, the individualization of HIPW is highly recommended in order to maintain PAP effects for 10-m sprint times, 30-m sprint times and agility times throughout the 10 minutes when compared to LIPW.